Efficiency improvement of a photovoltaic system by acting on the characteristics of MPPT control. (1st January 2013) - Aziz, A.; Aziz, El.M.; Zouggar, S.; Aboutni, R.; Tanouti, J.; Setti, M.
A 360 W photovoltaic (PV) module power with a maximum power point tracking (MPPT) algorithm is analysed and presented. In this study, the control algorithm is improved and then applied to the PV system. The results obtained show the ability of this algorithm to control high powers when weather conditions are changing. Under the same conditions, this improved technique offers, in steady state regime, a high dynamic tracking, but also a very satisfactory stability and precision of the MPP which has an improvement of the overall conversion system.